2018
DOI: 10.4236/fns.2018.91004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lion’s Foot (<i>Alchemilla vulgaris</i>) on Liver and Renal Functions in Rats Induced by CCl<sub>4</sub>

Abstract: The present work aims to study the influence of antioxidants activity of lion's foot (Alchemilla vulgaris) leaves at different concentrations to give more protection against chronic liver disease. Results indicated that dried lion's foot leaves had rich in total polyphenolic and flavonoids content (395.65 and 183.10 mg/100g, respectively). These results were reflected to the antioxidant activity (DPPH); it's noticed that the antioxidant activity of dried lion's foot leaves was high (131.74%). The major polyphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…These results are may due to the content of phyotchemicals as antioxidant and its activity (DPPH) in lion's foot which have a significant effect on lowering all lipids parameters except increase in HDL level. These data were in agreement of [4] and [11]. It could be noticed from the presented data in Table (3) that positive control (induced with CCl 4 ) showed a significant decrease of glutathione reductase activity (10.69ng/ml) compared to rats fed on basal diet (25.72ng/ml).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…These results are may due to the content of phyotchemicals as antioxidant and its activity (DPPH) in lion's foot which have a significant effect on lowering all lipids parameters except increase in HDL level. These data were in agreement of [4] and [11]. It could be noticed from the presented data in Table (3) that positive control (induced with CCl 4 ) showed a significant decrease of glutathione reductase activity (10.69ng/ml) compared to rats fed on basal diet (25.72ng/ml).…”
Section: Discussionsupporting
confidence: 85%
“…Fortification with dried lion's foot leaves and its extracts of water and ethanol on acceptability are shown also in Table (4). It was found that there was no significant statistical difference in sample pulp fortified with 1% dry leaves powder (91.83 ± 3.24) compared to control sample (94.00 ± 5.64) that recorded the best sample of fortified pulp followed by the other samples where there were no statistical differences between there samples., the values were (84.74 ± 5.26, 83.83 ± 6.55, 85.42 ± 6.50, and 82.87 ± 5.83, respectively).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…It is a member of the Rosaceae family and is rich primarily in flavonoids such as quercetin and kaempferol (Al-osaj, 2016), tannins, and chemical compounds such as gallic acid and ellagic acids (Neagu et al, 2015;Kostadinović et al, 2019). Dried lion's foot leaves have rich in total polyphenolic and flavonoids content (395.65 and 183.10 mg/100g, respectively) (El-Hadidy et al, 2018). The antioxidant, anti-inflammatory, anti-microbial and the anti-carcinogenic effects of the A. vulgaris have been attributed to its flavonoid components (9.8 mg/g) (Havsteen, 2002;Pietta, 1998).…”
Section: Introductionmentioning
confidence: 99%